Evaluation of Anti-Obesity and Antidiabetic Activities of Orostachys japonicus in Cell and Animal Models - Ramakanta Lamichhane; Prakash Raj Pandeya; Kyung-Hee Lee; Gopal Lamichhane; Jae-Young Cheon; Hyo Shin Park; Nguyen Quoc Tuan; Hyun-Ju Jung (MDPI AG, 2024)
Orostachys japonicus is a popular traditional medicinal herb used in Asian countries. This study is focused on evaluating its role in lipid and glucose metabolism in cell and animal models to establish the plant as an anti-obesity and antidiabetic herb. A butanol fraction of O. japonicus was used in the study. The lipid production was evaluated by the Oil Red O technique while the expression of adipogenic markers by Western blotting and RT-PCR using 3T3-L1 preadipocyte. The effect on glucose uptake activity was evaluated in C2C12 myoblast cells. The animal study was carried out in C57BL mice to evaluate anti-obesity activity using the high-fat diet model. The evaluation of serum lipid, blood glucose, adipogenic and fibrosis markers in the liver, and fat deposition in the liver and adipose tissue (by histology) of mice was conducted. Butanol fraction of O. japonicus significantly inhibited the lipid production in the 3T3-L1 cells and reduced the expression of PPARγ, C/EBPα, SREBP-1c and aP2. It enhanced glucose uptake in insulin-resistant C2C12 myoblast cells. It reduced body weight, triglycerides, and blood glucose in the obese mice. It significantly inhibited lipid accumulation in the liver and adipose tissue of obese mice along with suppression of expression of adipogenic and fibrosis markers in the liver. In summary, supporting the previous results, this study helped to establish the potent anti-obesity, antidiabetic, and liver-protecting effect of the butanol fraction of O. japonicus.